Therapeutic Self-Disclosure within DBT, Schema Therapy, and CBASP: Opportunities and Challenges - Köhler, Stephan; Guhn, Anne; Betzler, Felix; Stiglmayr, Christian; Brakemeier, Eva-Lotta; Sterzer, Philipp (Frontiers in Psychology, 2017)
In recent years, various therapeutic interventions have been established that extended behavior and cognitive behavior therapy (CBT) by so-called “third-wave” strategies. In order to address specific therapeutic challenges in certain subgroups of patients who do not sufficiently respond to “classical CBT,” some of these third-wave strategies put particular emphasis on therapist self-disclosure. This article highlights therapeutic self-disclosure as a means to address interpersonal problems by comparing three third-wave strategies: (a) acceptance and change strategies as used in Dialectical Behavioral Therapy (DBT), (b) the concept of “limited reparenting” as used in Schema Therapy (ST), and (c) disciplined personal involvement as used in the Cognitive Behavioral Analysis System of Psychotherapy (CBASP). On the basis of a critical discussion on opportunities and challenges within these three concepts, self-disclosure is proposed to be a promising therapeutic tool that is worth to be investigated in more depth in future studies.